Formação continuada dos agentes educacionais da educação básica pública do estado do Rio Grande do Sul: a experiência da formação continuada macromissioneira - Angst, Francisco (2018)
The present research focused its efforts on the Education Agents of the basic education of the State of Rio Grande do Sul through the study of the Program of Continuing Education Macromissioneira, executed by the Federal University of Fronteira Sul in partnership with Instituições de Ensino Superior (IES) of the region Northwest of the same state. Initially, it was necessary know historically and legally the structuring and composition of this segment of education professionals, rescuing their origin and knowing their current composition. Following the study, a parallel was drawn between the offered training and the training guidelines established by resolution of the Higher Education Chamber of the Ministry of Education. Next, the material produced by the public attended in the above-mentioned training program is presented, restricted to two Coordenadorias Regionais de Educação (CRE) of the area served (14th CRE and 36th CRE). The purpose of this study structure is to show how the elaboration and institutional execution of the Program for the training of this public of educational professionals, forgotten in the school space and school management, can serve as a reference, among others, for the social recognition and appreciation of their performance in the educational environment and to promote public policies aimed at these professionals.